PERILAKU JUDI ONLINE (DIKALANGAN MAHASISWA UNIVERSITAS RIAU) - Adli, Maulana; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was carried out among University Students of Riau. In order to determine the behavior of online gambling among college students. Problems in this study are (1) Who are the students who conduct online gambling activities? (2) What are the factors that encourage students to conduct online gambling? (3) What is the impact of online gambling on college student activity after online gambling addiction or gambling? This research is a qualitative descriptive ,. As for the population in this study is Riau University student who engages in gambling online. Because the number of students who perform online gambling is not known, in this study the authors in the sampling technique used non probability that Snowball Sampling technique by determining one or two informants to be interviewed further from previous informant informant further information. This will continue until the time when the informant is sufficient. To collect the data the researchers used the method of observation, documentation, and in-depth interviews using interview guideline in analyzing the research data used in the analysis of qualitative and described in descriptive writing.Based on the results of this study concluded that online gambling behaviors among university students in this study is riau students aged 21-25 years.Based on the results of this study concluded that online gambling behaviors among students that is caused by factors, factors lax parental control, profit factor, the desire and the entertainment factor. And the impact of the behavior of online gambling is that health impacts, reduce the spirit of learning, economic, personality and lead to deviant behavior like that is lying, pawning goods as well as the positive impact of online gambling is that as entertainment.Keywords: Behavior of online gambling, among students